The Encyclopedia of world history ancient, medieval, and modern, chronologically arranged - Stearns, Peter N.; Langer, William L. (William Leonard) 1896-1977 (Houghton Mifflin, 2001)
Completely expanded and revised, this indispensable guide to all human history now includes a searchable compact disc of the entire text and maps for quick search of dates, places, and peoples